Dynamic soaring mechanisms in the ocean boundary layer. (2016) - Bonnin, Vincent; Benard, Emmanuel; Toomer, Christine A.; Moschetta, Jean-Marc
Dynamic soaring is a flying technique which extracts energy from an environment where wind gradients form, such as the air-sea interface above oceans that sees such gradients developing through multiple and combined phenomena. Models of wind-wave interactions are analysed in terms of their influence on the induced wind field, before selecting a purely sinusoidal peak wave from the wave spectrum and developing the related wind field using stable laminar theory. Dynamic soaring trajectories are then derived by optimising a nonlinear constrained problem that models the evolution of a point mass vehicle. Characteristic phases of dynamic soaring flight are evidenced out of the overall trajectories and compared to the flat-ocean case in order to conclude on the influence of waves regarding dynamic soaring performances.